2002
DOI: 10.1177/0272431602022001004
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors Associated with Disordered Eating During Early Adolescence

Abstract: Risk and protective factors associated with disordered eating were examined among 363 girls (X age =12.9 years) in middle-level school. The variables included self-report ratings of competence and of the importance of physical appearance and social acceptance by peers, self-oriented and socially prescribed perfectionism, negative events, and parental support. In a multivariate regression analysis, low competence in physical appearance, high importance of social acceptance, high self-oriented perfectionism, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 46 publications
10
68
2
2
Order By: Relevance
“…Our results depart from those of McVey et al, who found that SOP, but not SPP (from the children's version of the MPS), was associated with higher levels of dietary restraint and weight/food preoccupation in a sample of young adolescents. 26 However, our results are similar to those of other investigations which found that the associations between SPP and eating disturbances are stronger among female college students and young females with high BD. 39 Our study makes a significant contribution to the literature because it relates the most known mediators of disordered eating behaviors in adolescents (perfectionism, SE, BMI, and BD).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results depart from those of McVey et al, who found that SOP, but not SPP (from the children's version of the MPS), was associated with higher levels of dietary restraint and weight/food preoccupation in a sample of young adolescents. 26 However, our results are similar to those of other investigations which found that the associations between SPP and eating disturbances are stronger among female college students and young females with high BD. 39 Our study makes a significant contribution to the literature because it relates the most known mediators of disordered eating behaviors in adolescents (perfectionism, SE, BMI, and BD).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have already shown an association of disordered eating with perfectionism in community samples, 7,8,24 as well as with BD 25 and with SE. 26 The strength of the present study is its simultaneous attention to all these relevant variables in the same participants. We observed that total ChEAT scores correlated significantly with BMI, corroborating previous studies that found higher scores on the ChEAT questionnaire 27 or other measures of eating pathology 28 among overweight vs. normal-weight children.…”
Section: Discussionmentioning
confidence: 95%
“…Because of the weak correlation with DE, social support does not appear to be a protective factor in the development of eating disorders for adolescents from the general population [22] or athletes. Regarding self-esteem, the absence of significant differences between athletes and controls is unexpected in light of studies that indicate higher self-esteem in the former in comparison to the latter (e.g., [37]) as well as in elite athletes compared with non-elite athletes and non-athletes [38].…”
Section: Discussionmentioning
confidence: 88%
“…Although significantly fewer studies have considered male participants, very similar patterns of influence have been found in adolescents of both sexes (e.g., [12]). However, a high level of social support has been considered an important protective factor from ED (e.g., [22]) despite the lack of studies of athletes showing this variable as a possible predictor of ED.…”
Section: Introductionmentioning
confidence: 99%
“…attractiveness is thought to play a prominent role in promoting and maintaining a number of body image-related problems (e.g., McVey, Pepler, Davis, Flett, & Abdolell, 2002;Thompson, Heinberg, Altabe, & Tantleff-Dunn, 1999;Wertheim, Paxton, & Blaney, 2004). Today's beauty standards are not only portrayed as highly important but are difficult and near impossible to achieve (Wolf, 1991).…”
mentioning
confidence: 99%